Evaluating the development, woman-centricity and psychometric properties of maternity patient-reported outcome measures (PROMs) and patient-reported experience measures (PREMs): A systematic review protocol. Issue 2 (10th February 2022) - Bull, Claudia; Teede, Helena; Carrandi, Lane; Rigney, Azure; Cusack, Sally; Callander, Emily
Abstract : Introduction: Woman-centred care is the right of every woman receiving maternity care, irrespective of where care is being received and who is providing care. This protocol describes a planned systematic review that will identify, describe and critically appraise the psychometric properties of maternity patient-reported outcome measures (PROMs) and patient-reported experience measures (PREMs). The woman-centricity of PROM and PREM development and content validation (ie, the extent to which women were involved in these processes) will also be assessed. This information will be used to develop a maternity PROMs and PREMs database to support service and system performance measurement, and value-based maternity care initiatives. Methods and analysis: This study will be guided by the COnsensus-based Standards for the selection of health Measurement INstruments (COSMIN) guideline for systematic reviews of outcome measurement instruments. Studies identified via MEDLINE, CINAHL Plus, PsycINFO and EMBASE describing the development, content validation and/or psychometric evaluation of PROMs and PREMs specifically designed for maternity populations throughout pregnancy, childbirth and postnatal periods will be considered if published from 2010 onward, in English, and available in full text. The COSMIN risk of bias checklist will be used to evaluate the quality of studies reporting on the development, content validation and/or psychometric evaluation of PROMs and PREMs. COSMIN criteria for good content validity will be used to assess the woman-centricity of PROM and PREM development and content validation studies. COSMIN standards of good psychometric properties will be used to evaluate the validity and reliability of the identified instruments. Ethics and dissemination: Ethical permission for this research is not required. The findings of this research will be submitted for publication in an international, peer-reviewed journal. Abstracts for national and international conference presentations will also be submitted. The proposed maternity PROMs and PREMs database will be freely accessible online, and developed with consumer input to ensure its usefulness to a range of maternity care stakeholders. PROSPERO registration number: CRD42021288854.